Determination of Quality of Life for Thalassemic Adolescent - Kafi Mohammed Nasir; Wamed Hamed Shaker (Kufa Journal for Nursing Sciences)
Background: Thalassemia major is a prevalent hereditary disease in Mediterranean region, so that the assessment of quality of life, especially in those with chronic illnesses such as thalassemia is particularly important.